Abrine, an IDO1 inhibitor, suppresses the immune escape and enhances the immunotherapy of anti-PD-1 antibody in hepatocellular carcinoma - Liang, Xiaowei; Gao, Hongwei; Xiao, Jian; Han, Shan; He, Jia; Yuan, Renyikun; Yang, Shilin; Yao, Chun (Frontiers in Immunology, 2023)
Indoleamine-2,3-dioxygenase 1 (IDO1) is responsible for tumor immune escape by regulating T cell-associated immune responses and promoting the activation of immunosuppressive. Given the vital role of IDO1 in immune response, further investigation on the regulation of IDO1 in tumors is needed. Herein, we identified that the important immune and inflammatory response cytokine interferon-gamma (IFN-γ) up-regulated the IDO1 expression in cancer cells through the methylation of 6-methyladenosine (m6A) m6A modification of RNA, metabolism of Tryptophan (Trp) into kynurenic acid (Kyn), and JAK1/STAT1 signaling pathway, which could be inhibited by IDO1 inhibitor Abrine. CD47 is IFN-γ-stimulated genes (ISGs) and prevents the phagocytosis of macrophages, leading to the cancer immune escape, and this effect could be inhibited by Abrine both in vivo and in vitro. The PD-1/PD-L1 axis is an important immune checkpoint in regulating immune response, overexpression of PD-1 or PD-L1 promotes immune suppression, while in this study Abrine could inhibit the expression of PD-L1 in cancer cells or tumor tissue. The combination treatment of Abrine and anti-PD-1 antibody has a synergistic effect on suppressing the tumor growth through up-regulating CD4+ or CD8+ T cells, down-regulating the Foxp3+ Treg cells, and inhibiting the expression of IDO1, CD47, and PD-L1. Overall, this study reveals that Abrine as an IDO1 inhibitor has an inhibition effect on immune escape and has a synergistic effect with the anti-PD-1 antibody on the treatment of HCC.